2015
DOI: 10.1515/afe-2015-0090
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Shell Thickness, Insulation and Casting Temperature on Defects Formation During Investment Casting of Ni-base Turbine Blades

Abstract: Turbine blades have complex geometries with free form surface. Blades have different thickness at the trailing and leading edges as well as sharp bends at the chord-tip shroud junction and sharp fins at the tip shroud. In investment casting of blades, shrinkage at the tip-shroud and cord junction is a common casting problem. Because of high temperature applications, grain structure is also critical in these castings in order to avoid creep. The aim of this work is to evaluate the effect of different process pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…23 The results are in agreement with a previous work. 24 In general the cavity located at the 12 o'clock position in the bottom-gated set-up was filled to a greater extent than the cavity in the 6 o'clock position, as can been seen Figure 5a. However, a significant difference in the castings in the 12 o'clock and 6 o'clock positions is observed in setup 4 where misalignment in hanging was adjusted, as described in the footnotes of Table 1.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…23 The results are in agreement with a previous work. 24 In general the cavity located at the 12 o'clock position in the bottom-gated set-up was filled to a greater extent than the cavity in the 6 o'clock position, as can been seen Figure 5a. However, a significant difference in the castings in the 12 o'clock and 6 o'clock positions is observed in setup 4 where misalignment in hanging was adjusted, as described in the footnotes of Table 1.…”
Section: Resultsmentioning
confidence: 73%
“…The material properties for the mould material were taken from a previous study 15 as shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Modification of high silicon (Si) alloys is performed to refine Si particles morphology in the eutectic phase. At very thin wall thickness level, cooling rate tends to be high and leads to high shrinkage velocities, as the speed goes above the threshold shrinkage velocity then pores will form, and very limited time given for diffusion to take place hence porosity is formed whether you have a grain refiner or not [5]. Even though thickness level below 2 mm possess high driving force nucleation, which may lead to finer grains [6] that should have been in assistance to promote good feeding at interdimeric regions [7], you also have high shrinkage velocities which leads to shrinkage porosity.…”
Section: Introductionmentioning
confidence: 99%